PENGARUH AUDIT FORENSIK, PROFESIONALISME AUDITOR, DAN KOMITMEN ORGANISASI TERHADAP PENDETEKSIAN FRAUD - Nur Ma'rifah; Andy Setiawan (Veteran Economics, Management, & Accounting Review, 2022)
This study is a quantitative study that aims to examine the effect of forensic audit, auditor professionalism, and organizational commitment on fraud detection. This study uses auditors in the Main Investigation Auditorat of the Supreme Audit Agency of the Republic of Indonesia (BPK RI) as a sample. Saturated sampling was used in sampling and used primary data through a questionnaire which obtained a total of 37 auditors. The analysis technique in this study uses Structural Equation Modeling - Partially Least Square (SEM-PLS) using WarpPLS software version 8.0 and a significance level of 5% (0.05). The results of the test show that (1) forensic audit and auditor professionalism have a significant influence on fraud detection and (2) organizational commitment does not have a significant effect on fraud detection.Keywords: Forensic Audit; Auditor Professionalism; Organizational Commitment; Fraud Detection This study is a quantitative study that aims to examine the effect of forensic audit, auditor professionalism, and organizational commitment on fraud detection. This study uses auditors in the Main Investigation Auditorat of the Supreme Audit Agency of the Republic of Indonesia (BPK RI) as a sample. Saturated sampling was used in sampling and used primary data through a questionnaire which obtained a total of 37 auditors. The analysis technique in this study uses Structural Equation Modeling - Partially Least Square (SEM-PLS) using WarpPLS software version 8.0 and a significance level of 5% (0.05). The results of the test show that (1) forensic audit and auditor professionalism have a significant influence on fraud detection and (2) organizational commitment does not have a significant effect on fraud detection. Keywords: Forensic Audit; Auditor Professionalism; Organizational Commitment; Fraud Detection